Optimization Design of 600 Wp Solar Tree System Design According to Tilt Angle - Iskandar, Handoko; Taryana, Een; Subhan, Alwan Naufal; Ramadhan, Farhan; Ramadhan, Muhammad Badai (Universitas Negeri Gorontalo, 2025)
This paper describes the design optimization of the 600 Wp Solar Tree System, with a focus on determining the optimal tilt angle. The purpose of this study is to analyze and determine the optimal tilt angle and evaluate the performance of the system in three different locations on the campus of Universitas Jenderal Achmad Yani (UNJANI). The methods used in this study include analysis of solar radiation data at 0° azimuth and different tilt angles (15° to 30°) using PVSyst. software and system performance parameters such as Solar Fraction (SF), Performance Ratio (PR), and Normalized Production. Based on the results, the optimal tilt angle is 15° with a maximum annual solar irradiation of 1912 kWh/m². Performance simulations of the three sites showed similar results, with all three sites producing the best performance with 92.66% SF and 57.76% PR. The system generated the lowest unused energy of 199.56 kWh/year. The research conducted gives important guidelines for optimizing the design of the 600 Wp Solar Tree System implemented on the collages